Partial Least Square Method-Structural Equation Model for Assessment of Drivers of Digital Marketing Adoption by Indian SMEs - Priyanka Pradhan, Dr. Devesh Nigam, Dr. C.K. Tiwari (International Journal of Advanced Science and Technology, 2020)
Let’s start with Google! Google Trends enlighten with the fact that Google gathers information as well as gives an opportunity to compare among the options (Jun et al., 2014). Google Trends, a brand new source of massive knowledge, has showed that frequently of digital marketing as a search term increased from 2004 to 2018 comparison with all other search terms in diﬀerent regions and languages.